(untitled) (Journal of the College of Basic Education, 2022)
The complexity of human life in our contemporary society has exacerbated life’s difficulties, man’s problems have multiplied, burdens have increased, and it has become difficult for man to fulfill most of his needs and aspirations or to walk in life without suffering or pain. Our society and the challenges facing this society, the successive wars, aggression, destruction, and so on, have increased human suffering and intellectual and psychological conflicts, as well as increased psychological stress, frustration, anxiety, deprivation, depression, a sense of psychological loneliness, alienation, a sense of brokenness and psychological defeat.